(untitled) (Analele Universității București.Filosofie, 2025)
Drawing on a variety of philosophers from Plato to Ricoeur, the authors suggest that philosophy based on poetry or image can be intellectually valuable in the following ways: They show how an intentional approach to imagistic, spiritual philosophy can promote consideration of beauty, engage the productive imagination, and ultimately alter one’s engagement with the human predicament. This spiritual mode of philosophy does not stop in an aesthetic (the appetites) frame, but works through it productively.